A highly efficient bimetallic/biochar composite with enhanced catalytic reforming of pyrolysis tar: Performance and mechanism. (September 2022) - Zhang, Jun; Chen, Junjie; Chen, Zhengrui; Xiong, Qinyi; Di, Yingchen; Yin, Linlin; Tian, Yu
Abstract: In this study, a highly efficient bimetallic Ni-Fe/char composite catalyst has been synthesized successfully for catalytic cracking of pyrolysis tar and displays excellent catalytic cracking performance with tar conversion efficiency of 95.6 % (35.2 % of H2 yield). The results showed that at the steam/carbon ratio, the reaction temperature and gas residence time of 1.0, 800 °C and 0.5 s respectively, the bimetallic char-supported catalysts showed outstanding catalytic performance compared with traditional catalyst, in which the N6F6/C exhibited the best activity under the same conditions. The catalytic mechanism of NiFe based catalysts can be attributed to the formation of a NiFe alloy. Furthermore, the synergy of Ni and Fe contributed to greater activity for toluene cracking and enhancement of fuel-gas yield. Bimetallic NiFe alloy catalysts have a promising potential for application as highly efficient catalysts for tar removal and reutilization via catalytic cracking. Graphical abstract: Unlabelled Image Highlights: Highly porous carbons derived from biomass pyrolysis were fabricated. Optimal parameters were selected by univariate analysis and orthogonal design. The formation of NiFe alloy inhibited the deactivation of nickel nanoparticles. H2 yield of 35.2 % and toluene conversion of 95.6 % were obtained over Ni6Fe6/char.